(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This study explores the linguacultural features of gastronomic metaphors in the English language from the perspectives of conceptual metaphor theory and cultural linguistics. Gastronomic metaphors constitute a cognitively grounded and culturally embedded domain through which abstract concepts are structured and evaluated. The research aims to identify dominant conceptual mappings between the source domain of gastronomy and various target domains such as emotions, morality, intellect, social hierarchy, and interpersonal relations. The methodology combines qualitative semantic analysis, discourse-contextual interpretation, and linguacultural modeling. The empirical data include 200 metaphorical expressions extracted from literary texts, journalistic discourse, and spoken corpora of contemporary British and American English. The findings demonstrate that gastronomic metaphors are organized around systematic conceptual models (e.g., EMOTIONS ARE TASTES, IDEAS ARE FOOD, SOCIAL VALUE IS INGREDIENT). While grounded in embodied experience, these metaphors are shaped by historically and culturally specific Anglo-American traditions. The study contributes to cognitive linguistics and linguaculture studies by highlighting gastronomy as a culturally marked semantic field reflecting the English linguistic worldview.